Charles Richard Vaughan correspondence - Vaughan, Charles Richard, 1774-1849.
Letter (1826 January 2) written by Vaughan to sculptor William John Coffee cancelling a contract with him; letter (1827 June 13) from Vaughan to Charles Stuart, Baron Stuart de Rothesay, discussing diplomatic affairs in London, England, and Washington, D.C., and commenting on American reaction to the death of British prime minister George Canning; and fragment of a letter (1831 April 29) written by an unknown correspondent upon Vaughan's departure from Washington, D.C.
British diplomat.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Fragment was previously cataloged separately.
Keywords: Canning, George, -- 1770-1827 -- Death and burial; Coffee, William John, -- 1774-1846? -- Correspondence; Stuart de Rothesay, Charles Stuart, -- Baron, -- 1779-1845 -- Correspondence; Diplomatic and consular service, British -- United States; Sculpture, American -- 19th century; Great Britain -- Foreign relations -- United States; United States -- Foreign relations -- Great Britain; Diplomats -- Great Britain